The Discipline Character in the Prayer Movements of Hyperactive Children in State Special School (SLB) Ungaran and Kemala Bhayangkari 90 Kindergarten Semarang Police Academy - Wakhidah, Laelatul Maulidil; Khamidun, Khamidun (BELIA: Early Childhood Education Papers, 2018)
Hyperactive children tend to act at will and never realize the risk they will get. This matter causes some parents doubt to teach prayers or even introduce the prayer movements little by little to hyperactive children. The practice of prayer requires discipline so the child can do it according to what it should be. Therefore, based on the explanation above, the purpose of the study is to describe the character of discipline in the prayer movement of hyperactive children and explain the supporting and inhibiting factors of the discipline character in prayer movements of hyperactive children. The type of the research is qualitative which focuses on the discipline character of hyperactive children prayer movement. The data collection techniques used are interviews, observation, and documentation and the data analysis techniques by data reduction activities (data reduction), data presentation (data display) and conclusions (verification) Based on the research results conducted on hyperactive children, shows that children have not been able to do the prayer movements properly and correctly. This is due to the lack of awareness in the child and the role of parents to teach the prayer movement. Therefore, from observations made when prayer learning process at school, children have not been involved in performing the prayer movement. According to the results that have been stated, it shows that the discipline character in the prayer movement of hyperactive children in the research has not seen yet in children. This is caused by many factors, such as the environment and the children awareness.